Using network toxicology and molecular docking to identify core targets and pathways underlying tacrolimus-induced tremor in organ transplant recipients - Chao Liu; Qian Chen; Fu Yan; Yulin Niu (Scientific Reports)
Abstract Tacrolimus, the most commonly prescribed immunosuppressant following organ transplantation, is associated with various neurotoxic effects, notably tremor, which significantly impacts the quality of life of recipients. The precise mechanisms underlying tacrolimus-induced tremor remain unclear. To investigate this, we employed network toxicology and molecular docking methodologies to identify potential targets and pathways. The SMILES representation of tacrolimus was retrieved from the PubChem database, and toxicity predictions were performed using ProTox-3.0 and ADMETlab 3.0. Targets related to tacrolimus and tremor-associated diseases were identified from public databases. Protein-protein interaction networks and functional enrichment analyses were conducted using STRING and Cytoscape. Molecular docking studies were carried out with CB-Dock2. A total of 43 potential targets associated with tacrolimus exposure and tremor were identified, out of which five core targets were filtered through STRING and Cytoscape analyses: AKT1, GBA, SCN8A, SCN2A, and SCN4A. Functional enrichment analysis highlighted several critical pathways implicated in tacrolimus-induced tremor, including the Dopaminergic synapse, Parkinson’s disease, Rap1 signaling pathway, Spinocerebellar ataxia, and Apoptosis. The results of molecular docking indicated that tacrolimus exhibits the strongest binding affinity toward SCN8A and SCN2A among the core targets. This study suggests that tacrolimus-induced tremor may be closely linked to parkinsonian tremor and provides a theoretical foundation for understanding the neurotoxic effects of tacrolimus. Given the limited research in network toxicology on the specific molecular mechanisms involved, further animal studies are warranted to elucidate these mechanisms in detail.